A Pseudoaneurysm of a Peripheral Artery Arising Four Years After Trauma to a Limb: A Case Report. Issue 1 (January 2016) - Bhuyan, Sanjeev K.; Dey, Sukalyan; Baruah, Pradip K.; Bordoloi, Bikash J.
Abstract : Case: A young woman who underwent plate fixation for a radial shaft fracture had an uneventful recovery for four years. Subsequently, over a four-month period, a slowly progressing swelling appeared in the forearm with no features of vascular insufficiency, bruits, or pulsatility. Doppler ultrasonography and computed tomography revealed a pseudoaneurysm arising from the ulnar artery. The patient was treated with exploration, evacuation of the clot, aneurysm repair, and implant removal. Conclusion: To our knowledge, this is the longest period of quiescence reported for a posttraumatic pseudoaneurysm. A late pseudoaneurysm is possible in previously operated limbs, even after years of recovery and the absence of the typical features of vascular lesions.